2018
DOI: 10.5301/ejo.5001027
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and normal values of static pupil diameters

Abstract: This study provides reference values for age- and light-related pupil diameters measured with the PupilX digital pupillometer in normal subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
(38 reference statements)
0
13
0
3
Order By: Relevance
“…Since pupillary resting diameter reflects the balance between opposing sympathetic and parasympathetic autonomic systems, the decrease in PD as age increased might have been related to either increasing parasympathetic effects or decreasing sympathetic input. Additionally, in a recent study, Schroder et al showed that this decrease in PD with age is largest for scotopic (≈0.057 mm/year) and smallest for photopic illumination (≈0.025 mm/year).…”
Section: Discussionmentioning
confidence: 94%
“…Since pupillary resting diameter reflects the balance between opposing sympathetic and parasympathetic autonomic systems, the decrease in PD as age increased might have been related to either increasing parasympathetic effects or decreasing sympathetic input. Additionally, in a recent study, Schroder et al showed that this decrease in PD with age is largest for scotopic (≈0.057 mm/year) and smallest for photopic illumination (≈0.025 mm/year).…”
Section: Discussionmentioning
confidence: 94%
“…Pupillometry devices can be used to obtain automatic, multiple, quantitative measurements of pupillary response to light under controlled, ambient lighting conditions. This improves the repeatability of the examinations, solves the problem of clinician‐dependent errors and reduces false negative responses …”
Section: Discussionmentioning
confidence: 99%
“…Objektif pupilla değerlendirmesi için kullanılan pupillometri cihazları, kontrollü ortam aydınlatması koşullarında ışığa verilen pupil yanıtlarının otomatik, çoklu, kantitatif ölçümlerini elde edebilmektedir. 8,9 Pupillometri cihazları, pupillar ölçümlerinin tekrarlanabilirliğini artırmakta ve yanlış negatif yanıtları azaltmaktadır. 8,9 Diyabetik otonom nöropati, diyabetin genellikle zor tanınan komplikasyonlarından biridir ve kardiyovasküler, gastrointestinal, sudomotor ve oküler otonom sinirleri etkileyerek morbidite ve mortaliteye neden olabilmektedir.…”
Section: Gereç Ve Yöntemlerunclassified
“…8,9 Pupillometri cihazları, pupillar ölçümlerinin tekrarlanabilirliğini artırmakta ve yanlış negatif yanıtları azaltmaktadır. 8,9 Diyabetik otonom nöropati, diyabetin genellikle zor tanınan komplikasyonlarından biridir ve kardiyovasküler, gastrointestinal, sudomotor ve oküler otonom sinirleri etkileyerek morbidite ve mortaliteye neden olabilmektedir. 4,5 Özellikle kardiyak semptomları olan diyabetik hastalarda görülmektedir ve tanısı konmamış kardiyak otonom nöropatili hastalarda mortalite riski çok yüksektir.…”
Section: Gereç Ve Yöntemlerunclassified
See 1 more Smart Citation